Pendaftaran Peralihan Hak Atas Tanah Berdasarkan Akta Pengikatan Perjanjian Jual Beli di Kota Padang - Elittrosint, Vicia (Alhurriyah, 2020)
Each Land Office has a different policy in accepting return registration of certificates based on PPJB, some accept and some reject. Based on this description, the author is interested in discussing this thesis with the title "Registration of Transfer of Land Rights Based on the Binding Deed of Purchase Agreement at the National Land Agency Office in Padang City." The problem is, How is the Process of Making a Sale and Purchase Binding Agreement (PPJB) for Registration of Land Rights In Kota Padang, How Is Legal Strength Against Proof of Binding of Contract of Purchase (PPJB) In the Process of Registration of Transfer of Land Rights at the National Land Agency Office in Padang City, What Is the Process for Registration of Transfer of Land Rights in the Deed Phase of the Binding Agreement of Purchase (PPJB) in Padang City National Land Agency Office. The writing of this thesis uses empirical juridical methods that determine the field in court with the legal aspects or regulations that apply with respect to the object of research. Copyright and implementation of the Registration of Transfer of Land Rights Based on the Binding Deed of Purchase Agreement at the Office of the National Land Agency in Padang City has not been fully implemented properly or it has not been effective.